Strategi Belajar dalam Berpidato Bahasa Korea: Studi Kasus pada Mahasiswa Berprestasi di Lingkungan Program Studi Pendidikan Bahasa Korea - Shema Alisya Maharani; Didin Samsudin; Asma Azizah (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to explore the language learning strategies used by students in delivering Korean speeches. The research uses a mixed-method approach, combining qualitative and quantitative methods, and was conducted in the Program Studi Pendidikan Bahasa Korea at the Universitas Pendidikan Indonesia. It involved 21 students who had won Korean speech competitions at both international and national levels, placing from first to fourth. To assess their speaking strategies, the SILL (Strategy Inventory for Language Learning) questionnaire by Oxford (1990) was adapted. Additionally, interviews were conducted to gather more detailed information. The findings show that metacognitive strategies were the most commonly used, with an average score of 3.2, indicating a high usage level. These strategies include self korean speech practice that supports the successful speech delivery. Other strategies also used at high levels include memory strategies (3.1), cognitive strategies (3.0), affective strategies (2.9), compensation strategies (2.7), and social strategies (2.7). This study suggests that Korean language learners aiming for success in speech delivery can apply these strategies.